Reversible addition–fragmentation chain transfer (co)polymerization of conjugated diene monomers: butadiene, isoprene and chloroprene. Issue 1 (30th June 2016) - Moad, Graeme
Abstract : This review provides a critical survey of the literature on reversible addition–fragmentation chain transfer (RAFT) (co)polymerization of industrially significant conjugated diene monomers, specifically butadiene, isoprene and chloroprene. There is a focus on polymerizations performed in heterogeneous media. However, experiments on RAFT solution or bulk (co)polymerization are also included in the survey. A goal common to much recent work in this area has been to define the polymerization conditions necessary to minimize crosslink formation, thereby providing a low‐dispersity polymer with defined architecture and composition while, at the same time, achieving an acceptable (i.e. maximizing) monomer conversion and polymerization rate. © 2016 Society of Chemical Industry Abstract : This review presents a critical survey of RAFT (co)polymerization of conjugated diene monomers, focusing on the conditions necessary to minimize crosslinks and provide low‐dispersity polymers with well‐defined structure whilst maximizing polymerization rate.